Modeling and Analysis of Inverse Kinematics for Three Degrees of Freedom Ankle Joint Auxiliary Rehabilitation Device based on Ball Pair - Wang Liangwen; Song Kangkang; Shi Changmin; Wang Caidong; Du Wenliao (Jixie chuandong)
In order to realize ankle recovery,a kind of auxiliary device for ankle rehabilitation based on a ball pair is developed. The device adopts the center ball pair as the support,and 3S’PS’ branch chain as drive system,the three-dimensional motion of the working platform can be formed,and the dorsal flexion/plantar flexion movement,varus/valgus movement and adduction/abduction movement can be realized for ankle. Based on introducing the structure of the rehabilitation device,an inverse kinematic modeling and analysis for the device are performed. Arming at the multiple kind of movement patterns of system,an inverse kinematic modeling and analysis are completed respectively. The related calculation formulas are deduced and relation charts of motion angle between working platform and motor are plotted by using the Matlab. The research process provides a reference for the mechanism analysis of similar structure.